2013
DOI: 10.5007/1980-0037.2013v15n6p639
|View full text |Cite
|
Sign up to set email alerts
|

Enxágue bucal com carboidrato não melhora o desempenho em sprints repetidos

Abstract: The objective of this study was to evaluate the effect of a carbohydrate mouth rinse on the repeated sprint ability (RSA) of young soccer players. Nine youth soccer players (15.0 ± 1.5 years; 60.7 ± 4.84 kg; 1.72 ± 0.05 m; 20.5 ± 1.25 kg/m 2 ) were selected. The athletes were submitted to an RSA test consisting of six sprints of 40 m (going/ return = 20 m + 20 m), separated by 20 s of passive recovery, under three experimental conditions: carbohydrate mouth rinse (CHO) or placebo (PLA) and control (CON). The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…In studies conducted with futsal (De Oliveira et al, 2020) and football (De Oliveira et al, 2019) players, it was found that post-activation potentiation application positively affected repetitive sprint running performance, on the other hand, combination of the application and CHO-MR has been shown to have no additive effect. Similarly, in a study testing performance of 6 × 40 m sprints (round trip = 20 m + 20 m) divided by 20 s of passive recovery, it was found that CHO-MR had no significant effect on repeated sprint performance compared to placebo and control sessions (Bortolotti et al, 2013). Cherif et al (2018) revealed that 5 × 5s × 2sets (3 min rest between sets, 25 s rest between sprints) performed in the fasting state, CHO-MR (10% maltodextrin) performed before each sprint in the maximal sprint protocol does not have a significant influence on sprint performance.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In studies conducted with futsal (De Oliveira et al, 2020) and football (De Oliveira et al, 2019) players, it was found that post-activation potentiation application positively affected repetitive sprint running performance, on the other hand, combination of the application and CHO-MR has been shown to have no additive effect. Similarly, in a study testing performance of 6 × 40 m sprints (round trip = 20 m + 20 m) divided by 20 s of passive recovery, it was found that CHO-MR had no significant effect on repeated sprint performance compared to placebo and control sessions (Bortolotti et al, 2013). Cherif et al (2018) revealed that 5 × 5s × 2sets (3 min rest between sets, 25 s rest between sprints) performed in the fasting state, CHO-MR (10% maltodextrin) performed before each sprint in the maximal sprint protocol does not have a significant influence on sprint performance.…”
Section: Discussionmentioning
confidence: 98%
“…They have reported that only CHO consumption is more likely to give a beneficial performance effect. Bortolotti et al (2013) and Clarke, Kornilios, and Richardson (2015) stated that the stimulus produced by CHO-MR may not be strong enough to affect short-term and high-intensity training. Although it is known that CHO-MR has the ability to mechanically stimulate the motivation centers (orbitofrontal cortex) in the brain (De Pauw et al, 2015), with the method constructed from the results obtained in this study, it seems that the stimuli used are insufficient to affect the outcome variables of physical performance.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy men on a 3‐day intermittent fasting state, MR with 10 ml of 6.4% CHO solution before each sprint (2×5×5 s, inter‐repetition rest: 25 s, inter‐set rest: 3 min) for 5 s was found not to differ from the control and PLA interventions in the measured repeated sprint variables (Cherif et al, 2018). In young football players, 10‐s CHO‐MR (6% maltodextrin) immediately and 5 min before the 6×40 m sprint test separated by 20‐s active recovery did not show significant effect on best sprint time, mean sprint time, and FI (Bortolotti et al, 2013). Similarly, CHO‐MR had no effect on repeated sprints with direction changes (de Oliveira et al, 2019), single or four VJs, short sprints, or shuttle running (Přibyslavská et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, CHO‐MR had no effect on repeated sprints with direction changes (de Oliveira et al, 2019), single or four VJs, short sprints, or shuttle running (Přibyslavská et al, 2016). Bortolotti et al (2013) and Clarke et al (2015) stated that the stimulus generated by CHO‐MR may not be strong enough to influence short‐duration and high‐intensity exercises. The finding of no significant difference between interventions in our study and ES at a trivial‐medium level can be explained by a similar mechanism (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation